Fast radio bursts as cosmological proxies: estimating the hubble constant - Piratova-Moreno, Eduard Fernando; García, Luz Ángela; Benavides-Gallego, Carlos A.; Cabrera Blandón, Ana Carolina (Frontiers in Astronomy and Space Sciences, 2025)
One of the most challenging problems in modern cosmology is the Hubble tension, a discrepancy in the predicted expansion rate of the Universe with different observational techniques that results in two conflicting values of H0. We leverage the sensitivity of the Dispersion Measure (DM) from Fast Radio Bursts (FRBs) with the Hubble factor to investigate the Hubble tension. We build a catalog of 98 localized FRBs and an independent mock catalog and employ three methods to calculate the best value of the Hubble constant: i) the median value of H0 derived from direct computation combined with bootstrap resampling, ii) the Maximum Likelihood Estimate (MLE), and iii) the reconstruction of the cosmic expansion history H(z) using two DM-z relations previously explored in the literature. The values found vary between 53 and 80 km/s/Mpc. The result with the best statistical precision (6.0%) is the one obtained through MLE: H0=70.10−3.63+4.19 km/s/Mpc. On the other hand, when using 100 mock catalogs of 500 simulated FRBs in each realization, we obtain a value for the Hubble constant changes to H0=67.30−0.85+0.98 km/s/Mpc. More importantly, the latter result notably increases the statistical precision to 1.5% (the same level of precision as reports from the SH0ES collaboration). Ultimately, the rapid increase in the number of confirmed FRBs will provide us with a robust prediction of the value of the Hubble parameter today, which, in combination with other cosmological observations, will allow us to alleviate (to a certain degree) the current Hubble tension and make inference of other cosmological observables.